Finite Element Evaluation of the Femoral Neck System as Prophylactic Fixation to Prevent Contralateral Hip Fractures. (12th October 2022) - LaMonica, Julia N.; Rhee, Brian; Milligan, Kenneth; Leslie, Michael; Tommasini, Steven M.; Wiznia, Daniel H.
Introduction: Hip fractures cause significant morbidity and mortality for geriatric patients, and incidence is increasing as the population ages. Following a primary hip fracture, up to 20% may suffer a contralateral hip fracture within 5 years despite fracture risk reduction measures, including fall prevention and osteoporosis pharmacologic treatment. The aim of this study is to assess whether insertion of the Femoral Neck System (Depuy Synthes, West Chester, PA) into the contralateral proximal femur may strengthen the bone and decrease the incidence of contralateral hip fractures. Materials and Methods: ScanIP, an image processing software was used to produce 3-dimensional models of a cadaver femur with the implanted device. Models were meshed and exported to Abaqus for finite element analysis to evaluate the device's ability to reduce stress in the proximal femur. Results were analyzed for element-wise volume and von-Mises stresses. Results: The implant reduced peak stress and bone failure at all levels of bone quality. Specifically in osteoporotic bone, the implant decreased peak stress by 27%, proximal femur trabecular bone failure by 5% and cortical bone failure by 100% in the femoral neck. Conclusions: Our results from computer generated finite element analyses indicate that the Femoral Neck System may strengthen an osteoporotic proximal femur in the event of a lateral fall. Further investigation with expanded finite element analysis and cadaveric biomechanical studies are needed to validate these results.